If only you could bottle it memoirs of a radical son - Porter, Jack Nusan 1944- (Cherry Orchard Books, 2023)
"This memoir of a radical Jew follows Jack Nusan Porter's journey from his birth in Ukraine during the Holocaust, through the radical 60s and 70s, to the present day, and details his experiences fighting anti-Semitism, anti-Zionism, xenophobia, and hate"--
Keywords: Porter, Jack Nusan; Jewish sociologists / United States / Biography; Political activists / United States / Biography; Rabbis / United States / Biography; Radicalism / United States / History / 20th century; Sociologues juifs / États-Unis / Biographies; Activistes / États-Unis / Biographies; Rabbins / États-Unis / Biographies; Radicalisme / États-Unis / Histoire / 20e siècle; Jewish sociologists; Political activists; Rabbis; Radicalism; United States